PENGEMBANGAN LKPD MODEL PJBL PADA MATERI SISTEM PERNAPASAN MANUSIA DI SMP NEGERI 8 SATAP TONDANO - Olivia Tatanggihe; Ni Wayan Suriani; Fransiska Harahap; Jovialine A Rungkat; Zusje W. M Warouw (SOSCIED, 2023)
This research aims to develop teachinf LKPD media on respiratory system material for class VIII junior high school in science subjects. The aim of this research is to develop student worksheets using a suitable project based learning model. The type of research used is research and development with the ADDIE development model following the research stages according to Dick and Carry, namely (1) Analyze, (2) Design, (3) Development, (4) Implementation, (5) Evaluation.This research was carried out at SMP Negeri 8 Satap Tondano. This research instrument used a questionnaire consisting of a material expert questionnaire, a media expert questionnaire and a questionnaire for product trials (small groups). Based on the material expert questionnaire assessment of the developed LKPD, the assessment results were 78.33% and the media expert assessment was 93.75% in the very good category and suitable for use in the field. Then a small group trial consisting of 7 students at SMP Negeri 8 Satap Tondano obtained a result of 82.96%, so it can be concluded that the Student Worksheet product with the Project Based Learning model is suitable for use in the science learning process for junior high school students with system material human breathing.